Skin manifestations of COVID‐19 in children: Part 1. (1st April 2021) - Andina, D.; Belloni‐Fortina, A.; Bodemer, C.; Bonifazi, E.; Chiriac, A.; Colmenero, I.; Diociaiuti, A.; El‐Hachem, M.; Fertitta, L.; van Gysel, D.; Hernández‐Martín, A.; Hubiche, T.; et al.
Summary: The current COVID‐19 pandemic is caused by the SARS‐CoV‐2 coronavirus. The initial recognized symptoms were respiratory, sometimes culminating in severe respiratory distress requiring ventilation, and causing death in a percentage of those infected. As time has passed, other symptoms have been recognized. The initial reports of cutaneous manifestations were from Italian dermatologists, probably because Italy was the first European country to be heavily affected by the pandemic. The overall clinical presentation, course and outcome of SARS‐CoV‐2 infection in children differ from those in adults as do the cutaneous manifestations of childhood. In this review, we summarize the current knowledge on the cutaneous manifestations of COVID‐19 in children after thorough and critical review of articles published in the literature and from the personal experience of a large panel of paediatric dermatologists in Europe. In Part 1, we discuss one of the first and most widespread cutaneous manifestation of COVID‐19, chilblain‐like lesions. In Part 2, we review other manifestations, including erythema multiforme, urticaria and Kawasaki disease‐like inflammatory multisystemic syndrome, while in Part 3, we discuss the histological findings of COVID‐19 manifestations, and the testing and management of infected children, for both COVID‐19 and any other pre‐existing conditions. Abstract : Click here for the corresponding questions to this CME article.